Psychosocial factors and work related sickness absence among permanent and non-permanent employees - Gimeno, D. (BMJ Group, 2004)
Study objective: To examine the association between psychosocial work factors and work related sickness absence among permanent and non-permanent employees by sex. Design: A cross sectional survey conducted in 2000 of a representative sample of the European Union total active population, aged 15 years and older. The independent variables were psychological job demands and job control as measures of psychosocial work environment, and work related sickness absence as the main outcome. Poisson regression models were used to compute sickness absence days' rate ratios. Setting: 15 countries of the European Union. Participants: A sample of permanent (n = 12 875) and non-permanent (n = 1203) workers from the Third European Survey on Working Conditions. Results: High psychological job demands, low job control, and high strain and passive work were associated with higher work related sickness absence. The risks were more pronounced in non-permanent compared with permanent employees and men compared with women. Conclusions: This work extends previous research on employment contracts and sickness absence, suggesting different effects depending on psychosocial working conditions and sex.